The Importance of Otherness in the Teaching of Religion in School: The Great Challenge for the Teacher - Figueroa, Héctor Alfredo (2020)
By looking around, it is possible to realize that what happens in the classrooms is the consequence of the society in which it is embedded. Interpersonal relationships, frequently damaged by different circumstances, are weakened as time goes by ending in complete indifference towards other people or aggression that is impossible to prevent. It seems that Religion as a subject cannot tear down these walls of individualism, and consequently, it is not succeeding in its attempt to create peace and bring people together. It is time to question our actions as social agents and educators to achieve a real change for all of us. In order to do this, the first proposal is to recognize ourselves as we are; only then can we recognize the others. In that way, we may act as real bridge builders to motivate the dialogue that leads to peace.